Intussuscepção ileocólica associada a torção mesentérica em um cão: Relato de caso - Hermeto, Larissa Correa [UNESP]; Padua, Santiago Benites [UNESP]; Freire, Diogo Helney; Mattei, Douglas Rodrigo (My University, 2012)
Mesenteric torsion is a rare disease in dogs whereas it is more common to affect large animals. The main clinical signs observed are acute, such as prostration and abdominal distension which evolve to a state of shock and death. This paper reports the mesenteric torsion in a dog that was presented to veterinary care with generalized acute abdominal pain of sudden onset. At the physical examination, signs of acute abdomen, rectal temperature of 35 oC, moderate dehydration, congested mucous membrane, and prostration were detected. Emergency therapy was instituted and radiographic and ultrasound examinations were requested. The radiography showed increase in the bowel diameter and an image suggestive of intussusception. The patient was referred to emergency exploratory laparotomy and obtained a definite diagnosis of ileocolic intussusception associated to mesenteric torsion. Due to the extent of intestinal dysfunction, the patient was euthanized on the operating table.
Ileocolic intussusception associated with mesenteric torsion in dog: Case report
Keywords: Acute abdomen; Circulatory shock; Intestinal surgery